U.S. Department of Education’s Teacher Education Reform: How Does Your Program Rate? - Marshall, James E.; Beare, Paul L.; Newell, Patrick (Educational (Re)naissance, 2012)
A response from the field to Secretary of Education Arne Duncan and President Barack Obama’s plan for teacher education reform and improvement as described in the document Our Future, Our Teachers (2011).